Bacterial microflora of freshwater fish originated from Usmas lake in Latvia - Terentjeva, Margarita; Eizenberga, Inga; Novoslavskij, Aleksandr; Strazdiņa, Vita; Valciņa, Olga; Ošmjana, Jevgēnija; Bērziņš, Aivars (2015)
The aim of the present study was to evaluate the bacterial contamination of gills, skin and content of gastrointestinal tract of freshwater fish. Altogether 31 fish samples, including European eel (n=11), Silver bream (n=3) and European perch (n=17) were collected between April and July in 2014 from Usmas lake located in West part of Latvia. For evaluation of bacterial load the number of TBC (total bacterial count) and Enterobacteriaceae genera in gills, skin and intestinal tract was enumerated. Presence of Salmonella spp., L. monocytogenes and Y. enterocolitica was analyzed according to the ISO methods. Among different fish species investigated TBC in gills, skin and intestinal samples ranged from 1.89 to 7.47 log CFU.g-1, from 0.66 to 8.47 log CFU.cm-2 and from 0.30 to 8.25 log CFU.g-1 accordingly. Number of Enterobacteriaceae genera in gills, skin and intestinal tract ranged from 0.7 to 5.78 log CFU.g-1, from 4.91 to 7.12 log CFU.cm-2 and from 0.70 to 7.47 log CFU.g-1, respectively. Number of TBC and Enterobacteriaceae in European eel samples of gills, skin and intestinal tract was significantly less than in Silver bream and European perch samples (P<0.05). Salmonella and Y. enterocolitica were not found in fish, while L. monocytogenes was isolated from one perch (1/ 17/ 6). [.].